Non-Extendability of Special Diophantine Triples Involving Octagonal Numbers - R. Radha; G. Janaki; M. Madhumika (Explorations in Diophantine Equations, 2023)
We search for three distinct polynomials with integer coefficients such that the product of any two numbers of the set subtracted with their sum increased by a non-zero integer is a perfect square.